Performance Of Micro Gas Turbine Combined Heat And Power Systems Fueled By Biofuels - Ibrahim, Idris Enagi (2019)
The global demand for utilisation of renewable energy fuels in gas turbines has been on the increase to secure a sustainable and pollution free environment, especially in Malaysia where abundant biomass is available. The research problems involves combustion difficulties faced while using biofuels and lack of sufficient small-scale CHP-MGT systems in rural locations running on these low grade biofuels. In this research work, a combustion chamber was improved and best geometry selected using ANSYS-FLUENT program, followed by experimental verification of the model. Fuel spray characterisation was performed using four sizes commercial diesel nozzle injectors 1- 4 gallon per hour (GPH) for diesel, palm biodiesel and vegetable oil blends with diesel (P10-P100). Development of two-staged micro gas turbine based vehicular turbochargers using Garrett GT25 for first stage and Holset H1C for second stage was performed. Furthermore, the experimental test and combustion characterisation for the first-stage MGT and two-stage CHP-MGT were performed based on temperature profile, emissions and acoustics measurements, while the development of high-speed alternator based on vehicular alternator was accomplished for electrical power output. For the nozzle and spray experimental analysis using diesel fuel as a benchmark, injector 2 was selected for the experiment based on its performance as it produces best combustion stability, moderate TIT and acceptable compressor and turbines power outputs. The results from first stage MGT emission and combustion analysis shows that performances of palm biodiesel, P60 and pre-heating of P100 (vegetable oil) at 100 °C, were found out to be comparable to that of diesel fuel in terms of efficiency, power outputs and emissions. While using combustion acoustics analysis for all the fuels, a new tool was developed to compare flame stability of biofuels to diesel as a reference fuel. The development of high-speed alternator reveals that friction coupling is most suitable and hence adopted for the MGT, because it produces the least friction losses and lowest vibration value of 33.5m/s2 at maximum alternator speed of 13037 rpm. Lastly, the full MGT-CHP system characterisation was achieved with the following performances parameters as 71.5W electrical output, 18.2kW thermal power output, 0.36kg/kWh SFC for hot air production, 400ppm CO emissions, 48ppm NOx emissions, 43.7% HRU efficiency and 28.9% overall system efficiency.